IFRP: an intrusion/fault tolerant routing protocol for increasing resiliency and reliability in wireless sensor networks. (9th September 2013) - Nabizadeh, Hamid; Abbaspour, Maghsoud
Limitations of sensors cause routing and data sending to the base station become one of the challenging issues in wireless sensor networks (WSNs). So far, many methods are proposed for routing in the WSNs, but security is not mentioned in the most of them. Moreover, the proposed secure routings either are used for specific attack or have a high overhead. In this paper, we present a new method for neighbour detection and key management, and introduce a routing called intrusion/fault tolerant routing protocol (IFRP). The routing is switched from single path to multipath in the face of malicious behaviour by local warden technique (LWT). Proposed protocol detects and isolates intruder or faulty nodes by utilising LWT and a centralised decision. Simulations show that the IFRP have a superior delivery ratio over the mechanisms with low overhead. Moreover, results illustrate that the method with extra overhead has very low delivery ratio improvement by just 1%.